Uma análise do conteúdo de razão e proporção em livros didáticos do ensino fundamental - Lazzaretti, Raiana (2022)
The content of ratio and proportion that is still taught in elementary school represents one of the contents with the greatest practical application in the daily lives of students, regardless of their profession or social level. In this context, the importance of the process of teaching and learning such contents is evident. Thus, the objective of this work is to analyze how the content of reason and proportion is developed in elementary school textbooks, comparing the editions before and after the Common National Curriculum Base (BNCC). The two collections analyzed were chosen because they have the largest number of copies purchased throughout Brazil, according to data from the National Education Development Fund. To carry out this qualitative analysis, seven criteria were developed that aim at the general study of the content and proposed activities. The main changes between the collections and the agreement of the last edition regarding the skills listed in the BNCC were also scored. It was concluded that in one of the collections, the edition previous to BNCC is compatible with what was expected according to the established criteria. In general, books prior to BNCC showed greater concern in addressing the content of ratios and proportions in the seventh year. The current books contained what we consider to be the minimum, to be in keeping with the BNCC's highlighted skill for content. Thus, an evolution of what will appear in the next editions is expected, given the longer time for the adequacy of the books, given the new document.